Association of migration status with quality of life among rural and urban adults with rare diseases: A cross-sectional study from China - Zhang, Huanyu; Chen, Shanquan; Dong, Dong (Frontiers in Public Health, 2022)
Background A considerable proportion of rare disease patients decide to migrate to access a definitive diagnosis or appropriate care, which could affect their quality of life in a long term. Objective To compare quality of life (QoL) between migrants and residents and explore the possible mechanism of how migration influence the QoL among rural and urban adults with rare diseases, respectively. Methods A cross-sectional study at national level was conducted in a study sample of 1150 adult patients in China. Migration was defined as being away from one’s original place of residence for at least 12 months. Patients who remained in their place of residence in the past 12 months (“resident”) were treated as a comparison group for “migrants”. Original area of residence (rural vs. urban) for both residents and migrants was used for comparison. The brief version of the World Health Organization Quality of Life instrument was used to measure QoL. Multiple linear regression analyses were adopted to assess the direct association between migration status and QoL after controlling for the confounders that affect QoL. The indirect associations between migration status and QoL, mediated by potential mediators including number of family members living together, individual income, catastrophic health expenditure, and social support, were estimated using the mediation model. Results Among the group of rural participants, migration was directly associated with physical QoL (β=5.39, 95%CI 2.05 8.73) and environmental QoL (3.45, 0.68 6.22), indirectly associated with physical QoL (0.73, 0.15 1.53) and social QoL (0.50, 0.01 1.18) via individual income, and also indirectly associated with environmental QoL (0.52, 1.13 -0.10) via tangible support. On the other hand, neither direct nor indirect associations of migration with four domain scores of QoL were significant among the group of urban participants. Conclusions Among rural adults with rare diseases, migration was found to have positive direct effect on physical and environmental QoL, positive indirect effect on physical and social QoL through increased individual income, and negative indirect effect on environmental QoL via reduced tangible support. By contrast, neither direct nor indirect associations of migration with QoL were significant among the group of urban participants.